OUTBREAK OF HUMAN BRUCELLOSIS IN BOSNIA AND HERZEGOVINA: EVALUATION AND IMPORTANCE OF MICROBIOLOGICAL METHODS FOR THE DIAGNOSIS OF BRUCELLOSIS - Maida Šiširak (Peytchinski Publishing, 2020)
Purpose: Brucellosis is a worldwide zoonosis. In Bosnia and Herzegovina first cases of brucellosis were registered in 2000, since than disease is in an expansion. After the implementation of the program for mass vaccination of animals in 2009, the incidence of human brucellosis rapidly decreased, but only a few years. After some period of decreasing brucellosis, in 2017 and 2018 a new outbreak of brucellosis was registered. The aim of this study was to analyze epidemiological characteristics of patients in the last outbreak of brucellosis and diagnostic value of blood culture, Rose Bengal test and immunoenzymatic test (ELISA IgM and IgG). Patients and methods: This study included 181 brucellosis patients from January 2017 to September 2018. The disease was diagnosed by positive blood culture results, or by positive and relevant serologic test results. Results: The average age of patients was 45.72 years of life-range from 1 to 78. The gender distribution of patients was: 123/181 (67.96%) males and 58/181 (32.04%) females. Of the total of 181 studied patients, blood culture was requested for 112 (61.8%) of patients and in 37/112 (33%) were positive. The Rose Bengal test was positive in all patients 181/181(100.0%). Brucella IgM antibodies with ELISA were positive in 64/181(35.35%), while IgG antibodies were positive in 161/181(88.95%) of patients. Conclusion: Our results showed that sensitivity of test methods was different in the different stages of illness and so only combination of blood culture, the Rose Bengal test and ELISA ensured early and precise diagnosis of human brucellosis.